Characterization of biochar of pine pellet - Santos, Lidya B.; Striebeck, Maria V.; Crespi, Marisa S. [UNESP]; Ribeiro, Clovis A. [UNESP]; De Julio, Marcelo (Springer, 2015)
Recently, biochar was introduced as a bioadsorbent material to remove various contaminants in effluents, such as pigments, dyes, heavy metals, naphthalene, 1-naphthol, atrazine, phosphorus and some macro- and micronutrients. Therefore, biochar of biomass residue pellet obtained for slow pyrolysis was evaluated as an alternative process for the potential utilization as chemical contaminant remover with low cost. Thus, the main objective of this work was to produce biochar from pine residue pellet for subsequent use of the same as a potential adsorbent for effluent treatment. In order to perform the characterization, samples of biochar from pine pellet were produced using several heating rates (5-30 A degrees C min(-1)), residence temperatures (200, 280 and 570 A degrees C) and residence times (1 h and half an hour). The process adopted led to a rapid degradation of the raw material (pine pellet) associated with an intense generation of volatile compounds, conditions that led to a reduction in density and establishment of porous structure. Biochars had basic character (pH 8.47), predominance of aromatic structures, low moisture content (0.9-1.8 %), low ash content (1.25-1.80 %) and high thermal stability. Low humidity favors the adsorption and an improvement in the conservation during transport and storage.
Keywords: Biochar of biomass residues; Pyrolysis; Pine pellet; Thermal behavior